Comparing the Performance of Two Radiomic Models to Predict Progression and Progression Speed of White Matter Hyperintensities - Shao, Yuan; Ruan, Jingru; Xu, Yuyun; Shu, Zhenyu; He, Xiaodong (Frontiers in Neuroinformatics, 2021)
PURPOSE: To comparing two radiomics models in predicting progression of white matter hyperintensity (WMH) and the speed of progression from conventional magnetic resonance images. METHODS: Herein, 232 people were retrospectively analyzed at Medical Center A (training and testing groups) and Medical Center B (external validation group). A visual rating scale was used to divide all patients into WMH progression and non-progression groups. Two regions of interest (ROIs)—ROI whole-brain white matter (WBWM) and ROI WMH penumbra (WMHp)—were segmented from the baseline image. For predicting WMH progression, logistic regression was applied to create radiomics models in the two ROIs. Then, age, sex, clinical course, vascular risk factors, and imaging factors were incorporated into stepwise regression analysis to construct the combined diagnosis model. Finally, the presence of a correlation between radiomics findings and the speed of progression was analyzed. RESULTS: The area under the curve (AUC) was higher for the WMHp-based radiomics model than the WBWM-based radiomics model in training, testing, and validation groups (0.791, 0.768, 0.767 vs. 0.725, 0.693, 0.691, respectively). The WBWM-based combined model was established by combining age, hypertension and rad-score of the ROI WBWM. And the WMHp-based combined model is built by combining age and rad-score of the ROI WMHp. Compared with the WBWM-based model (AUC= 0.779, 0.716, 0.673 in training, testing, and validation groups, respectively), the WMHp-based combined model has higher diagnostic efficiency and better generalization ability (AUC= 0.793, 0.774, 0.777 in training, testing, and validation groups, respectively). The speed of WMH progression was related to the rad-score from ROI WMHp (r = 0.49) but not from ROI WBWM. CONCLUSION: The heterogeneity of the penumbra could help identify the individuals at high risk of WMH progression and the rad-score of it was correlated with the speed of progression.